WEBLIOGRAPHY: NEW FORMATS OF PRESENTATION BIBLIOGRAPHY IN THE WEB ENVIRONMENT - Korolova, Tetyana D. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article deals with the concept of «Webliography», and also discussed topical issues of creating Webliography in libraries. The operation of the Scientific Library of Admiral Makarov National University of Shipbuilding to create thematic Internet navigators.